2015
DOI: 10.1155/2015/703980
|View full text |Cite
|
Sign up to set email alerts
|

Blasting Vibration Monitoring of Undercrossing Railway Tunnel Using Wireless Sensor Network

Abstract: The construction blasting in a new tunnel will undoubtedly influence the structure of existing tunnel. In order to monitor the effect of the blast-induced vibration on the structure of existing tunnel, a wireless sensor network (WSN) was established, which included the blast vibration monitoring system and the wireless remote data acquisition system. An existing railway tunnel was monitored during the construction of a new tunnel in Shaanxi, China. Concrete strain and peak particle velocity (PPV) were adopted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 12 publications
1
31
0
1
Order By: Relevance
“…Meanwhile, the water intake point of west-route of the South-to-North Water Transfer Project is only dozens of kilometers away from Xinzhuangling tunnel, which will be unified with current irrigation system. On this occasion, the large increase of water will cause huge hidden danger for the safety of existential tunnels [37][38][39][40][41]. Therefore, performing the large-scale field soaking experiment near Xinzhuangling tunnel has great engineering significance.…”
Section: Description Of Test Fieldmentioning
confidence: 99%
“…Meanwhile, the water intake point of west-route of the South-to-North Water Transfer Project is only dozens of kilometers away from Xinzhuangling tunnel, which will be unified with current irrigation system. On this occasion, the large increase of water will cause huge hidden danger for the safety of existential tunnels [37][38][39][40][41]. Therefore, performing the large-scale field soaking experiment near Xinzhuangling tunnel has great engineering significance.…”
Section: Description Of Test Fieldmentioning
confidence: 99%
“…Therefore, the 10-fold cross-validation will be conducted 10 times to validate the model. In summary, the process of travel mode selection model based on the Bayesian network combining mutual information and expert knowledge is presented in Figure 2 [42][43][44][45][46].…”
Section: Bayesian Network Model Validationmentioning
confidence: 99%
“…Xuan et al [25] evaluated the uncon ned compressive strength, static elastic modulus, and indirect tensile strength of cement-treated C&D waste aggregates and concluded that this material has positive mechanical properties when used as a road base layer. Parallel to this, other authors have focused on assessing the feasibility of using C&D waste aggregates as subbase and base layers for asphalt concrete [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%